Experiences of primary education teachers on returning to school during the covid-19 pandemic - Ek, Judith (2022)
The purpose of this article was to describe the experiences of teachers in returning to classes during the covid-19 pandemic in a rural primary school in Yucatán, Mexico. The study was qualitative, based on an educational ethnographic study design. The information was obtained through semi-structured interviews addressed to six primary school teachers. The results were obtained by analyzing and categorizing the responses. Among the main results, the difficulties in adapting to hygiene standards and handling of children were observed, in the challenges and challenges the use of the face mask, the curricular modification, the lack of digital tools and the problems with connectivity, as well as the effects on health and experience on return. However, it is recognized that the adaptation of the curricular content contributes to continuing the teaching and learning process in person and at a distance. It concludes by attributing relevance in terms of the difficulties, challenges and challenges of returning to school, considering the influence of the conditions of the rural community where the primary school is located.